The Determination of User Retention to Use e-Wallet after COVID-19 Pandemic (Case Study of G-Wallet in Thailand) - Prompunthum, Pitch; Chirapanda, Suthawan (Journal of Ecohumanism, 2024)
The determinants of G-Wallet user retention has become important. This study examines the factors influencing user retention and the continued use of the G-Wallet application in Thailand. This research investigates the relationships between perceived usefulness, perceived ease of use, satisfaction, confirmation of expectation, relative advantage, compatibility, complexity, behavioral intention, and continuous use behavior. This research is quantitative research with 573 users. Key findings indicate that PU significantly enhances positive user attitudes towards G-Wallet, while PEoU has a negative effect on attitude, suggesting a complex relationship where ease of use may be perceived as diminishing the value of the application. COE positively impacts user satisfaction; however high satisfaction does not directly translate to a strong behavioral intention for continued use. RA and COMP positively affect behavioral intention, while complexity acted as a deterrent. Behavioral intention strongly predicts continuous use behavior, though satisfaction’s effect on continued use is significant.